Walk 2 DECEMBRISTS - -, - (project baikal, 2011)
Polkanov’s House. The House Transferred from Dekabrskikh Sobyty Street 47 to Dekabrskikh Sobyty Street 77 Tourist and Informational Center of Irkutsk City Administration The House located on Dekabrskikh Sobyty Street 77b Mini Park of the Symbols of Twin Cities Improvement of Dekabrskikh Sobyty Street in Irkutsk (between Yamskaya Street and Timiryaseva Street). Graduation Project